1999
DOI: 10.1161/01.cir.99.13.1733
|View full text |Cite
|
Sign up to set email alerts
|

Proatherogenic and Antiatherogenic Effects of Probucol and Phytosterols in Apolipoprotein E–Deficient Mice

Abstract: Background-The effects of probucol and a phytosterol mixture (FCP-3PI) on atherosclerotic lesion formation, plasma lipoproteins, hepatic and lipoprotein lipase activities, antioxidant enzyme activities, and plasma fibrinogen were investigated in apolipoprotein E-knockout (apoE-KO) mice. Methods and Results-Three groups of 8 mice were fed a diet containing 9% (wt/wt) fat (controls) or the foregoing diet supplemented with either 1% (wt/wt) probucol (the probucol group) or 2% (wt/wt) FCP-3PI (the FCP-3PI group) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 47 publications
6
122
3
1
Order By: Relevance
“…Previous studies have reported that probucol enhances lesion formation in the aortic root of female and male apoEϪ/Ϫ mice fed normal chow. 25,26 Consistent with that finding, lesions at this site were larger in probucol than control male mice fed a high-fat chow (Table I), although this difference did not reach statistical significance. Lesion size in the aortic root varied in the probucol group (Table I) owing to 2 animals with no lesions at all (not shown), whereas all other drug-treated animals had larger lesions than the largest individual control mouse.…”
Section: Aortic Morphometrysupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies have reported that probucol enhances lesion formation in the aortic root of female and male apoEϪ/Ϫ mice fed normal chow. 25,26 Consistent with that finding, lesions at this site were larger in probucol than control male mice fed a high-fat chow (Table I), although this difference did not reach statistical significance. Lesion size in the aortic root varied in the probucol group (Table I) owing to 2 animals with no lesions at all (not shown), whereas all other drug-treated animals had larger lesions than the largest individual control mouse.…”
Section: Aortic Morphometrysupporting
confidence: 75%
“…Lesion size in the aortic root varied in the probucol group (Table I) owing to 2 animals with no lesions at all (not shown), whereas all other drug-treated animals had larger lesions than the largest individual control mouse. Table I also shows that not only was the reported previously lesion-enhancing effect of probucol 25,26 confined to the aortic root region but also that probucol changed to become increasingly more antiatherogenic the more distal the site examined (Table I). At the abdominal aorta, probucol effectively prevented lesion formation.…”
Section: Aortic Morphometrymentioning
confidence: 83%
See 1 more Smart Citation
“…At the time of death, both native hearts and graft tissues as well as the kidneys and other tissues were appropriately collected and processed for histological examinations as previously described (30). Serial sections were cut and stained with hematoxylin and eosin and Masson's trichrome (31). The status of graft rejection was scored using the Billingham rejection grading system (47), including 0 (no rejection) to 3 (severe rejection).…”
Section: Methodsmentioning
confidence: 99%
“…O probucol é um potente antioxidante, capaz de reduzir a oxidação e internalização de LDL na íntima arterial, embora apresente incovenientes sobre o perfil lipídico (Moghadasian et al 1999;Bird et al 1998).…”
Section: )unclassified